A Systematic Mapping on Software Functionalities in Information Systems Used by Community Health Agents for Mouth Cancer Prevention - Viglio, Stephano Soares; Rodrigues, Pedro Augusto; Al Jawabri, Omar; Espindola, Vinicius Pereira; Figueredo, Leany Silva; Bulcão-Neto, Renato de Freitas; Ribeiro-Rotta, Rejane Faria; Graciano Neto, Valdemar Vicente (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: The adoption of digital technologies in the health domain can optimize data collection and storage processes, especially in the context of fieldwork carried out by Community Health Agents (CHA). Among the pathologies monitored, mouth cancer is one of them that, if detected early, can improve the patient’s prognosis. Problem: When analyzing the situation in Brazil, we notice an information gap in the state of the art regarding Information Systems (IS) specifically designed for the use of CHAs for collecting data from patients at high risk for mouth cancer. Solution: To advance towards the engineering of an IS to bridge this gap, we can elicit requirements collected from other IS currently used by CHAs reported in the literature. IS Theory: This study is based on General Systems Theory, since we examine the functionalities of health IS reported in primary studies. Method: A systematic mapping was conducted to identify requirements for healthcare ISs. Summarization of Results: Out of a total of 146 primary studies, 22 were selected, analyzed, and their data extracted. The results show that data collection is present in approximately 82% of the existing tools and applications. In addition, 45% of the studies report that automation and agility would contribute to the use of these devices, and 80% of the included studies mention personal data and symptoms or diseases as the main information to be extracted during home visits. Contributions and Impact on the IS Area: The results can serve as a reference for researchers and professionals seeking to implement solutions related to the Health IS domain.